UTILIZING ARTIFICIAL INTELLIGENCE IN THE TEACHING AND LEARNING OF ACCOUNTING AND BUSINESS EDUCATION TO DEVELOP ENTREPRENEURIAL MINDSET (NAU Journal of Technology and Vocational Education, 2026)
This paper provides a conceptual analysis of utilization of Artificial Intelligence (AI) in the teaching and learning of accounting and business education (A&BE) to develop entrepreneurial mindset (EM). As education systems evolve in response to technological advancement, the integration of AI into pedagogical practices has become imperative. Within A&BE, AI presents new opportunities for enriching instructional delivery, promoting innovation, and preparing learners for dynamic economic environments. The paper examines the strategic application of AI in fostering deeper understanding, problem solving, and critical thinking core elements of EM. It argues that AI-powered tools such as adaptive learning systems, automated assessments, and real-time data analytics can transform teaching methods and enhance students’ capacity to identify opportunities, take initiative, and create value within and beyond formal employment structures. Furthermore, the paper posits that the incorporation of AI into A&BE can bridge the gap between theory and practice in developing students’ EM. However, challenges such as inadequate infrastructure, limited digital literacy among educators, and ethical concerns must be addressed for effective implementation. The paper recommends among others that educational institutions should invest in reliable internet connectivity and modern AI tools to ensure seamless access for both students and educators. Regular professional development programs should be organized to equip teachers and students with the necessary skills and knowledge to effectively use AI technologies and continuous professional development for educators, and curriculum redesign to integrate AI-driven entrepreneurial competencies. It concludes that utilizing or leveraging AI in A&BE is not only timely but necessary for nurturing EM capable of driving innovation and national development in a technology-driven global economy.
Keywords: Accounting education; artificial intelligence; business education; entrepreneurial mindset; teaching; learning